(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Managing cemeteries is an important part of human settlement growth, as it involves various tasks such as grave digging, landscaping, scheduling, logistics, and record-keeping. To improve the process, researchers conducted a qualitative research study with a descriptive design, which involved surveying and interviewing staff members from the office cemetery, the health and sanitation department, and the health and sanitation department inspector. The researchers proposed introducing automated filling to the Tala office cemetery, as the manual filling system is disorganized and needs improvement. They suggest hiring employees with experience using technology, specifically Microsoft Word and other applications, and providing necessary equipment such as computers, internet connection, printer, and scanner. The proposed process would include manual and automated filling to improve workflow and organize records.